Breaking Down the Daily Use of Places - A Space-Time Typology of Temporary Populations in the Netherlands - Robbert Zandvliet; Martin Dijst (European Regional Science Association (ERSA), 2005)
In a network society, spurred on by technological, social, and economic factors, the process of land use deconcentration has resulted in various new urban forms such as edge cities and edgeless cities. While the consequences of this process for the distribution of the residential population and travel patterns have been extensively described and analyzed, there has as yet been little investigation of its effect on visitors' use of places. The aim of this study is to develop a typology of urban, suburban, and rural municipalities located in monocentric and polycentric urban systems on the basis of dimensions of diurnal weekday variations in visitor populations. The dimensions used in this study have been derived from the 1998 Netherlands National Travel Survey. A two-step cluster analysis resulted in five types of municipality: 'central place', 'contemporary node', 'self-contained', 'mobile children', and 'local children'. The results reveal that, compared with monocentric urban systems, settlements in polycentric urban systems are more networked; that is, suburbs in these systems are capable of attracting a substantial share of working visitors who have their residence in the core city ('contemporary node') and school children from other suburban and central city communities ('mobile children'). Outside the urban systems the 'self-contained' type, which contains people at work, learning, and in recreation locally and lacks the inflow of visitors from outside, is over represented.
Keywords: 330